2007
DOI: 10.1177/1744259106075233
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Microclimate by CFD Modeling of Moisture Interactions between Air and Constructions

Abstract: There is a strong demand for accurate moisture modeling since moisture poses a risk for both the constructions and the indoor climate. This investigation has special focus on moisture modeling. This study describes a new model based on a CFD tool enhanced to include both detailed modeling of airflows in rooms and heat and moisture transfer in walls by applying them as fluid walls. The impacts of different boundary conditions and how these influence microclimates in rooms are investigated, in a 3D configuration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
16
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 10 publications
0
16
0
Order By: Relevance
“…With the model, it was possible to predict the microclimate around valuable objects such as paintings. Other attempts of combining CFD and HAM can be found in Mortensen et al [13] and Defraeye et al [14]. Defraeye applied an external coupling procedure and used a separate CFD and HAM model which were then combined by transferring and setting the boundary conditions from one model to the other.…”
Section: Introductionmentioning
confidence: 99%
“…With the model, it was possible to predict the microclimate around valuable objects such as paintings. Other attempts of combining CFD and HAM can be found in Mortensen et al [13] and Defraeye et al [14]. Defraeye applied an external coupling procedure and used a separate CFD and HAM model which were then combined by transferring and setting the boundary conditions from one model to the other.…”
Section: Introductionmentioning
confidence: 99%
“…For example microclimates can occur near artefacts. A detailed study of these microclimates is necessary for the assessment of damage risks [11,12]. Most BES programs are typically multizone models: they represent a room as one node and have the assumption that state variables (e.g.…”
mentioning
confidence: 99%
“…An earlier investigation by computational fluid dynamics (CFD) showed that different placement of furniture near colder external walls may affect the RH in the microclimate and that the highest values were found when the furniture was placed directly on the floor and had a small distance to the wall [2]. There is a lack of empirical data of flow patterns behind furniture.…”
Section: Introductionmentioning
confidence: 98%